Persuasive Sentimental Method in the Electronic Newspapers of Terrorist Organizations - A research drawn from a Master Degree thesis - H. AL.Tameemi, Hashim; Hayder Faleeh, Kifah (ALBAHITH ALALAMI, 2025)
The paper probes into minute identification of the data of the methods followed in the electronic newspapers that aim to promote terrorist organizations like Al Qaeda and ISIS to draw emotional empathy and sympathy with them. The paper aims at identifying: How emotional empathy was utilized by terrorists in E-newspapers. How useful utilizing emotional empathy was in attracting supporters. The sample that is used in the paper is based on the opening articles of E-newspapers that propagate Al Qaeda and ISIS, e.g. (Sawtu el jihad) “The Sound of Fighting in the Name of God”, (Mua’skar el Battar wal Shamikha wal Khansaa) “Camps of Al Battar, Shamika, and Khansaa”, “Inspire” and (Thurwatu el Sanam, Dabiq, and Rumiyah).The paper is descriptive following the survey approach and data analysis approach. The paper has come up with the following findings: 1. The Terrorist Organizations Al Qaeda and ISIS used twelve promoting methods in the opening articles of the E-Newspapers; the emotional empathy method comes top among them. 2. They utilized the International World Web (Internet) to promote their methods and thinking via E-newspapers.